VOLATILITY AND WESTERN EUROPEAN PARTY SYSTEMS: TWO NEW APPROACHES - Lane, Jan-Erik (Baltic Journal of Political Science, 2015)
The sharp rise in electoral volatility in the last two decades calls for a new explanation of Western European party systems. The established party system theory—Lipset and Rokkan’s “freezing hypothesis”—is not confirmed by today’s data. But what framework should replace Lipset and Rokkan’s? One option is to focus on values in postmodern society, as French sociologist Alain Touraine does, by emphasizing how individualism trumps social cohesion formed by social cleavages. The rational-choice approach, combined with a principal-agent model perspective, offers another lens for exploring electoral volatility in Western Europe. In this paper, gross and net volatility are analysed with both Touraine’s sociological approach and with a new principal-agent model of political election, underlying dynamics.